2011
DOI: 10.1158/1940-6207.capr-11-0301
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-gallate Suppresses Tumorigenesis by Directly Targeting Pin1

Abstract: The most active anticancer component in green tea is epigallocatechin-3-gallate (EGCG). The human peptidyl prolyl cis/trans isomerase (Pin1) plays a critical role in oncogenic signaling. Herein, we report the X-ray crystal structure of the Pin1/EGCG complex resolved at 1.9 Å resolution. Notably, the structure revealed the presence of EGCG in both the WW and PPIase domains of Pin1. The direct binding of EGCG with Pin1 was confirmed and the interaction inhibited Pin1 PPlase activity. In addition, proliferation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
104
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 43 publications
0
104
0
Order By: Relevance
“…H1299 and CL13 lung cancer cells highly express G3BP1, and EGCG effectively suppresses anchorage-independent growth of these cells but was less effective in cells with a low expression of G3BP1 (131). Finally, we (113,119,139) found that EGCG binds with the human peptidyl prolyl cis/trans isomerase [Pin1 (139)], which plays a critical role in oncogenic signaling (40,128). In this case, we were able to combine crystallography, computational biology and cell-and animal-based studies to identify Pin1 as a novel binding protein of EGCG.…”
Section: Other Protein Targets Of Flavonoidsmentioning
confidence: 84%
“…H1299 and CL13 lung cancer cells highly express G3BP1, and EGCG effectively suppresses anchorage-independent growth of these cells but was less effective in cells with a low expression of G3BP1 (131). Finally, we (113,119,139) found that EGCG binds with the human peptidyl prolyl cis/trans isomerase [Pin1 (139)], which plays a critical role in oncogenic signaling (40,128). In this case, we were able to combine crystallography, computational biology and cell-and animal-based studies to identify Pin1 as a novel binding protein of EGCG.…”
Section: Other Protein Targets Of Flavonoidsmentioning
confidence: 84%
“…Clearly, it will be important to identify which active components and molecular targets/mechanisms may be responsible for the efficacy of strawberries. Such work has recently been reported in regard to the epigallocatechin gallate component of green tea (41).…”
mentioning
confidence: 76%
“…This method has been described previously (23,24). Briefly, PI3K active protein (2 µg) was reacted with Sepharose 4B beads or jugloneSepharose 4B beads in reaction buffer [50 mM Tris, pH 7.5, 5 mM ethylenediaminetetraacetic acid (EDTA), 150 mM NaCl, 1 mM dithiothreitol (DTT), 0.01% Nonidet P-40, 2 µg/ml bovine serum albumin, 0.02 mM phenylmethylsulfonyl fluoride (PMSF), and 1X proteinase inhibitor cocktail].…”
Section: Methodsmentioning
confidence: 99%